Pemenuhan Hak-Hak Anak dalam Kehidupan Pedagang Asongan Anak di Kecamatan Binjai Kota, Kota Binjai - Wigar Fakih Izati; Mia Aulina Lubis (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Children are the next generation of the nation who truly deserve to be protected and have their rights fulfilled. In Law No. 23 of 2002, this law regulates child protection in Indonesia. Through this law, children's rights are recognized and guaranteed, including the right to live, grow and develop, the right to education, the right to health, the right to protection from violence, exploitation and discrimination, and the right to participate. The aim of this research is to analyze the fulfillment of the rights of children who work as hawkers in Binjai Kota District based on theories, variables and realities that explain how children's rights are fulfilled in the lives of child hawkers. This research is of a qualitative type with data collection techniques in the research carried out by combining (triangulating) the process of in-depth interviews, observation and documentation. Then the data was analyzed by the researcher qualitatively and ended by drawing conclusions from the results of the research that had been carried out. The results of the research show that children's rights in the life of child hawkers are not fulfilled. It is recommended that the community continue to pay full attention to children who work as hawkers and also help reduce children's dependence on work as hawkers.